Influence of Social Media Marketing Capabilities on Business Performance: The Case Study of the Non-Life Insurance Products in South Africa - Datadin, Sanjeev (University of the Witwatersrand, Johannesburg, 2024)
In an evolving digital business landscape, the strategic utilisation of social media has become a vital competitive advantage for attracting customers and enhancing business performance. This study investigates the effectiveness of social media capabilities in pricing, product development, communication, planning, and implementation on business performance. The primary objective of this research is to determine the specific social media marketing capabilities that significantly influence business performance within the non-life insurance sector in South Africa. Employing a quantitative research approach, an online survey questionnaire was utilised to collect data, which was analysed through regression, structural equation modelling, and partial least squares structural equation modelling. Key statistical findings reveal that innovative pricing strategies (p-value = 0.001), product development (p-value = 0.028), planning (p-value = 0.046), and implementation capabilities (p-value = 0.004) positively influence business performance. However, social media marketing communication capability showed no significant impact (p-value = 0.978). Key findings unveil that innovative pricing strategies, product development, planning, and implementation capabilities positively influence business performance. Confirmatory Factor Analysis reinforces the interconnected nature of these capabilities, emphasising their collective and holistic impact on each other and the overall business performance. As non-life insurers navigate the highly competitive and evolving digital landscape in South Africa, a practical understanding of contextual factors shaping the effectiveness of social media marketing becomes imperative for growth and sustained competitiveness. The implications of these findings are significant, providing insurers with actionable insights to optimise their marketing strategies for enhanced performance. This research contributes to both theoretical and iii empirical knowledge by highlighting the critical factors that drive business success in the South African non-life insurance sector
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Non-life insurance; Marketing capabilities; Business performance; Social media marketing; SDG-8: Decent work and economic growth